The discovery of a non-competitive GOT1 inhibitor, hydralazine hydrochloride, via a coupling reaction-based high-throughput screening assay. (1st October 2022) - Wu, Qiqi; Sun, Zhongya; Chen, Zhifeng; Liu, Jingqiu; Ding, Hong; Luo, Cheng; Wang, Mingliang; Du, Daohai
Graphical abstract: Abstract: Glutamate oxaloacetate transaminase 1 (GOT1) plays a key role in aberrant glutamine metabolism. GOT1 suppression can arrest tumor growth and prevent the development of cancer, indicating GOT1 as a potential anticancer target. Reported GOT1 inhibitors, on the other hand, are quite restricted. Here, we developed and optimized a coupling reaction-based high-throughput screening assay for the discovery of GOT1 inhibitors. By using this screening assay, we found that the cardiovascular drug hydralazine hydrochloride inhibited GOT1 catalytic activity, with an IC50 of 26.62 ± 7.45 μM, in a non-competitive and partial-reversible manner. In addition, we determined the binding affinity of hydralazine hydrochloride to GOT1, with a Kd of 16.54 ± 8.59 μM, using a microscale thermophoresis assay. According to structure–activity relationship analysis, the inhibitory activity of hydralazine hydrochloride is mainly derived from its hydrazine group . Furthermore, it inhibits the proliferation of cancer cells MCF-7 and MDA-MB-468 with a slight inhibitory effect compared to other tested cancer cells, highlighting GOT1 as a promising therapeutic target for the treatment of breast cancer.